Organoleptic and physicochemical of meltique beef steak injected with varying concentrations of coconut oil - Permata Sari Dian; Apriantini Astari; Budiman Cahyo; Cipta Dainy Nunung; Humayrah Wardina; Lesa Aditia Edit (BIO Web of Conferences)
Meltique is a processed type of beef created by injecting vegetable fat to create marbling similar to the appearance of Wagyu beef. This technique enhances tenderness, and juiciness, while imparting a distinct flavor through the injected emulsion. However, the research on Meltique beef remains limited. This study aims to analyze the physicochemical and organoleptic properties of Meltique beef injected with coconut oil emulsions at two concentrations (365 g and 730 g) and to compare them with Wagyu beef. The study included malondialdehyde (MDA) analysis, antioxidant properties, Texture Profile Analysis (TPA), and a hedonic sensory test. Data were analyzed using a completely randomized design (CRD), with Tukey and Duncan tests employed for sensory analysis. The results demonstrated that varying coconut oil concentration affected the physicochemical and organoleptic properties of the beef. Notably, the 730 g coconut oil emulsion exhibited the highest antioxidant activity and the lowest MDA content. In the sensory evaluation, the meat injected with the 730 g emulsion was preferred for its aroma and tenderness. The use of coconut in the formulation retains beneficial high lauric acid content, presents a promising alternative for emulsion blends, and exhibits characteristics similar to Wagyu.